Foreign Body Ingestion in Children: Urgency of Management - Mazumder, Md Wahiduzzaman; Karim, ASM Bazlul; Rukunuzzaman, Md; Begum, Fahmida; Nahid, Khan Lamia (Bangladesh Journal of Child Health, 2019)
The majority of foreign body ingestions occur in children between the ages of six months and three years. Most cases are brought to medical attention by their parents because the ingestion was witnessed or reported to them. Commonly ingested objects include coins, button batteries, toys, toy parts, magnets, safety pins, screws, marbles, bones, and food boluses. Many of the children are asymptomatic or have transient symptoms at the time of the ingestion. A careful history and physical examination are the keystones in diagnosing an esophageal foreign body and to the prevention of its complications. Imaging can be used to confirm the findings and to localize the site of the foreign body. Clinical management focuses on identifying and treating the cases at risk for complications, which depends on the location and type of foreign body. Timing of removal depends on nature of ingested object and signs & symptoms of the airway/intestinal obstruction. Flexible endoscopy for most foreign body extractions is preferred. Bangladesh J Child Health 2019; VOL 43 (2) :106-112